1983
DOI: 10.1523/jneurosci.03-01-00237.1983
|View full text |Cite
|
Sign up to set email alerts
|

Strychnine blocks binaural inhibition in lateral superior olivary neurons

Abstract: The present study seeks to identify neurotransmitters mediating binaural inhibition in lateral superior olivary nucleus neurons. Neurons in this auditory structure receive inputs from both ears and are thought to code for localization of sound in space. Iontophoretic application of glycine during monaural stimulation was found to mimic the inhibition observed with binaural stimulation. Binaural inhibition was blocked by application of the glycine receptor antagonist, strychnine, as were the effects of iontopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
121
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(137 citation statements)
references
References 21 publications
14
121
0
2
Order By: Relevance
“…Numerous studies have demonstrated both a-subunit receptor immunoreactivity (Aoki et al, 1988) and high binding of 'H-strychnine in the LSO (Sanes et al, 1987;Glendennig and Baker, 1988). Electrophysiological data have shown the presence of strychnine-sensitive synapses in the LSO (Moore and Caspary, 1983;Wu and Kelly, 1991). Other studies have shown a high-affinity uptake of ?H-glycine in terminals in the LSO (Schwartz, 1985).…”
Section: Glycine Transporters In Glycinergic Nellrotransmissionmentioning
confidence: 97%
“…Numerous studies have demonstrated both a-subunit receptor immunoreactivity (Aoki et al, 1988) and high binding of 'H-strychnine in the LSO (Sanes et al, 1987;Glendennig and Baker, 1988). Electrophysiological data have shown the presence of strychnine-sensitive synapses in the LSO (Moore and Caspary, 1983;Wu and Kelly, 1991). Other studies have shown a high-affinity uptake of ?H-glycine in terminals in the LSO (Schwartz, 1985).…”
Section: Glycine Transporters In Glycinergic Nellrotransmissionmentioning
confidence: 97%
“…Two specialized nuclei of the SOC, the lateral superior olive (LSO) and the medial superior olive (MSO) are responsible for encoding ILDs and ITDs, respectively. The lateral superior olive (LSO), responsible for processing ILDs, consists of bipolar neurons excited by ipsilateral stimulation and inhibited by contralateral stimulation (Boudreau and Tsuchitani 1968;Moore 2000;Moore and Caspary 1983). The net result of excitatory and inhibitory inputs to each LSO encodes the range of ILDs, which can thus be further processed and interpreted at higher centres of the auditory system.…”
Section: Physiology Of Binaural Hearingmentioning
confidence: 99%
“…This fast, usually glycine-mediated inhibition is involved in coincidence detection (Brand et al, 2002;Pecka et al, 2008) and the temporally precise suppression of excitation (Tsuchitani and Boudreau, 1966;Boudreau and Tsuchitani, 1968;Moore and Caspary, 1983;Tollin and Yin, 2005). In the ascending pathways on the level of the dorsal nucleus of the lateral lemniscus (DNLL), GABAergic inputs suddenly generate an inhibition of a different time domain.…”
Section: Introductionmentioning
confidence: 99%